Association between illness perception and medication adherence in patients with diabetes mellitus in North Shoa, Zone: cross-sectional study - Eshete, Akine; Getye, Birhan; Aynaddis, Getachew; Tilaye, Bantalem; Mekonnen, Elda; Taye, Bethlehem; Zeleke, Dereje; Deresse, Tilahun; Kifleyohans, Tewodros; Assefa, Yibeltal (Frontiers in Public Health, 2023)
Background Although the impact of illness perception on medication adherence is well-established, its specific influence on medication adherence in Ethiopia remains unclear. Consequently, the objective of this study was to examine the association between illness perception and medication adherence among patients with diabetes mellitus in the North Shoa Zone. Methods An institution-based cross-sectional study was conducted from 24 May to 25 June 2022 in the North Shoa zone. The study included a random sample of 552 individuals with diabetes from four public hospitals. Data was collected and entered into Epi Data V.3.1, and analysis was performed using SPSS version 22. Descriptive statistics were used to summarize continuous variables as means with standard deviations, while categorical variables were presented as percentages. The study variables were analyzed using binary logistic regression models to assess the associations between illness perception and medication adherence. In the bivariable analysis, variables with p-values less than 0.20 were entered into a multivariable logistic regression model. Associations with a p-value ≤0.05 and an odds ratio with a 95% confidence interval were considered statistically significant. Results The study results revealed that medication adherence was 64.4% (95% CI: 60.1, 67.9), while illness perception was 54.7% (95% CI, 41.2, 49.4). There was a significant and strong association between illness perception and medication adherence (p < 0.0001). In the adjusted model, the illness perception components of consequence showed a significant association with medication adherence (AOR = 3.10, 95% CI: 2.11, 4.55). Similarly, personal control (AOR = 1.77, 95% CI: 1.20, 2.61) and emotional representation of diabetes (AOR = 2.26, 95% CI: 1.54, 3.32) were also significantly associated with medication adherence in patients with diabetes. Conclusion The findings of this study indicate a positive association between higher illness perception and increased medication adherence and practice. Therefore, when engaging in discussions about diabetic self-management, diabetes educators should employ psychoeducational approaches that take into account the illness perceptions of patients.